PENGARUH QUALITY OF WORK LIFE, KREATIVITAS, DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU DI SEKOLAH DASAR NEGERI (SE-KECAMATAN DRAMAGA KABUPATEN BOGOR) - Zikrine, Zikrine; Anwar, Saiful; Trihandayani, Estiningsih (Jurnal Manajemen Pendidikan, 2025)
Teacher performance is a key factor in determining the quality of primary education, as teachers play a direct role in the learning process. This study aims to analyze the effects of Quality of Work Life, creativity, and interpersonal communication on the performance of public elementary school teachers in Dramaga District, Bogor Regency. This research employed a quantitative approach with an associative design. The research population consisted of all public elementary school teachers in Dramaga District, with a total of 146 respondents selected using a census technique. Data were collected through closed-ended questionnaires using a five-point Likert scale and analyzed using multiple linear regression. The results showed that Quality of Work Life had a positive and significant effect on teacher performance with a significance value of 0.016, creativity had a positive and significant effect with a significance value of 0.002, and interpersonal communication had a positive and significant effect with a significance value of 0.039. Simultaneous testing indicated that Quality of Work Life, creativity, and interpersonal communication collectively had a significant effect on teacher performance with a significance value of 0.001. These findings indicate that improving the quality of work life, creativity, and interpersonal communication in an integrated manner plays an important role in enhancing teacher performance in elementary schools